THE EFFECTIVENESS OF CHICKEN FEET NUGGETS ON THE GROWTH OF CHILDREN AGED 1–3 YEARS AT TPMB U, CIMENYAN VILLAGE, BANDUNG REGENCY, 2025 - Dyah Triwidiyantari; Upit Upit (Jurnal Ilmiah Keperawatan, 2026)
Background: Nutritional problems among toddlers in Indonesia remain a serious concern. The 2024 Indonesian Nutritional Status Survey (SSGI) reported an increase in the prevalence of wasting and underweight, by 0.6% and 0.1% respectively. This condition highlights the urgent need for nutrition interventions based on local food sources to help meet the nutritional needs of children, especially in areas with limited access to nutritious food. Purpose: This study aims to analyze the differences in weight and height of children aged 1– 3 years between the intervention group and the control group after receiving chicken feet nugget supplementation Methods: A quantitative research design was used, specifically a quasi-experimental post-test only with control group. The sample consisted of 78 children aged 1–3 years, divided equally between the intervention and control groups. Data were analyzed using an independent T-test. Results: The results showed statistically significant differences between the intervention and control groups in both weight (p = 0.044; mean difference = 828.21 grams) and height (p = 0.049; mean difference = 3.15128 cm) Conclusion: In conclusion, the consumption of chicken feet nuggets was effective in improving the weight and height of children aged 1–3 years, and thus can serve as an alternative local food-based intervention to support child growth